Operations Management : Processes and Value Chains - Krajewski, Lee J. ; Ritzman, Larry P. and Malhotra, Manoj K. (Delhi Pearson Prentice Hall, 2016)
Operations Management provides students with a comprehensive framework for addressing operational process and supply chain issues. This text uses a systemized approach while focusing on issues of current interest.
Include Glossary and Index
Keywords: Production management -- Industrial management